Effects of Hybrid Graphene Oxide with Multiwalled Carbon Nanotubes and Nanoclay on the Mechanical Properties and Fire Resistance of Epoxy Nanocomposite - Tuan Anh Nguyen (Hindawi Limited, 2021)
In this study, nanoclay I.30E and multiwalled carbon nanotubes (MWCNT) were hybridized with graphene oxide (GO) on Epikote 240 epoxy resin. Research results show that the hybridization between 0.5 wt.% GO with 1 or 3 wt.% nanoclay and 0.05 wt.% MWCNT has better mechanical properties and flame-retardant properties than the component materials. The combination of epoxy nanocomposite materials with flame-retardant additives such as nanoclay, MWCNT, and GO leads to improving flame-retardant and mechanical properties. Flame-retardant materials have no environmental problems and are nontoxic. Therefore, the flame-retardant additives studied in this work have great potential to become one of the promising flame-retardant hybrid materials. The study also showed that the result of the combination, the hybridization between the three components (nanoclay, MWCNT, and GO) synergized the mechanisms of fire resistance, creating insulating barriers, preventing objects from entering material exposed to heat and oxygen in the air.